2016
DOI: 10.1188/16.onf.43-03ap
|View full text |Cite
|
Sign up to set email alerts
|

Factors Influencing Nurses’ Use of Hazardous Drug 
Safe-Handling Precautions

Abstract: Purpose/Objectives To identify factors associated with oncology nurses’ use of hazardous drug (HD) safe-handling precautions in inpatient clinical research units. Design Descriptive, cross-sectional. Setting The National Institutes of Health Clinical Center in Bethesda, Maryland. Sample 115 RNs working on high-volume HD administration units. Methods Survey data were collected online using the Hazardous Drug Handling Questionnaire. Data were analyzed using descriptive statistics and multiple regression … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
32
1
7

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(43 citation statements)
references
References 18 publications
3
32
1
7
Order By: Relevance
“…Our study showed great variability in the wearing of personal protective equipment and the steps performed in changing a diaper. These findings are in agreement with the literature [19,20]. For example, Polovich and Martin [21] highlighted that gloves were always worn for handling excreta, but other protective equipment was worn less often (e. g. gowns, 77 %; eye protection, 56 %; respiratory protection, 40 %).…”
Section: Discussionsupporting
confidence: 89%
“…Our study showed great variability in the wearing of personal protective equipment and the steps performed in changing a diaper. These findings are in agreement with the literature [19,20]. For example, Polovich and Martin [21] highlighted that gloves were always worn for handling excreta, but other protective equipment was worn less often (e. g. gowns, 77 %; eye protection, 56 %; respiratory protection, 40 %).…”
Section: Discussionsupporting
confidence: 89%
“…Younger nurses with fewer years of experience were more likely to use safety measures than older nurses with more years of experience. The relationship between participants’ age, years of experience, and safe-handling precautions is inconsistent in the literature (Callahan et al, 2016; Polovich & Clark, 2012; Rizalar et al, 2012). Lack of experience can increase risk for unnecessary exposure of cytotoxic drugs and contribute to the nurses’ safety (Rizalar et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…호장구 착용 정도가 높았고 15,16) 간호사 1인이 근무 시간 동안 담당 하는 환자 수가 많을수록 항암제 안전지침 이행 정도가 낮았다. 17) 또한 근로자들의 안전한 작업 수행은 환경적 요인의 영향이 큰데 18) 의료 환경도 이와 마찬가지로 간호사들이 병동 업무 환경을 안전 하다고 느낄수록 지침 이행에 긍정적인 영향을 미쳤으며 개인보호 장구(Personal Protective Equipment, PPE)의 접근성이 높을수록 지 침에 대한 이행이 높았다.…”
Section: 선행연구를 살펴보면 간호사의 자기효능감이 높을수록 개인보unclassified
“…17) 또한 근로자들의 안전한 작업 수행은 환경적 요인의 영향이 큰데 18) 의료 환경도 이와 마찬가지로 간호사들이 병동 업무 환경을 안전 하다고 느낄수록 지침 이행에 긍정적인 영향을 미쳤으며 개인보호 장구(Personal Protective Equipment, PPE)의 접근성이 높을수록 지 침에 대한 이행이 높았다. 15,16,19)…”
Section: 선행연구를 살펴보면 간호사의 자기효능감이 높을수록 개인보unclassified